IoT Smart Health for Monitoring and Control of Temperature and Humidity of Vaccine and Drug Storage based on Android at Health Center - Sindung HW Sasono; Ari Sriyanto Nugroho; Eko Supriyanto; Abu Hasan (Politeknik Negeri Semarang, 2022)
Abstract—Pharmacy service is one of the activities at the puskesmas (Public Health Center) that supports quality health services. One of the pharmaceutical activities is the storage of drugs and vaccines. The drug and vaccine storage room pays great attention to conditions, temperature sanitation, light, humidity, ventilation, to ensure product quality and staff safety. Most of the drugs in the puskesmas should be stored at room temperature between 18-28°C and air humidity 40% - 60%. The monitoring system built uses DHT22 as a room temperature and humidity detector. The sensor output is connected to the NodeMCU ESP8266 which acts as a microcontroller. While the control system uses a relay module as a liaison for the AC remote control and as an automatic switch. The room temperature and humidity control test is carried out using an existing air conditioner for the power on/off and temperature up/down functions. In addition, testing of room temperature and humidity control uses 2 different AC brands from 2 rooms. The test was carried out in the drug and vaccine storage room at the Pudak Payung Public Health Center. The test results show that the sensor can record data accurately and can be integrated with the transceiver device properly. Sending sensor data to the database has an average delay at each node of 21 seconds and sending sensor data to the database has good data loss quality, namely 9.68% for the vaccine room node, 13.4% for the medicine room, and the average temperature and humidity. Vaccine room is 24°C and 60%, while in Medicine room is 26°C and 50%. And the average temperature and humidity in the Vaccine room were 24°C and 60%, while in the Medicine room it was 26°C and 50%. This difference occurs due to several factors such as the location of the room, the area of the room, and the number of people in the roomAbstract—Pharmacy service is one of the activities at the puskesmas (Public Health Center) that supports quality health services. One of the pharmaceutical activities is the storage of drugs and vaccines. The drug and vaccine storage room pays great attention to conditions, temperature sanitation, light, humidity, ventilation, to ensure product quality and staff safety. Most of the drugs in the puskesmas should be stored at room temperature between 18-28°C and air humidity 40% - 60%. The monitoring system built uses DHT22 as a room temperature and humidity detector. The sensor output is connected to the NodeMCU ESP8266 which acts as a microcontroller. While the control system uses a relay module as a liaison for the AC remote control and as an automatic switch. The room temperature and humidity control test is carried out using an existing air conditioner for the power on/off and temperature up/down functions. In addition, testing of room temperature and humidity control uses 2 different AC brands from 2 rooms. The test was carried out in the drug and vaccine storage room at the Pudak Payung Public Health Center. The test results show that the sensor can record data accurately and can be integrated with the transceiver device properly. Sending sensor data to the database has an average delay at each node of 21 seconds and sending sensor data to the database has good data loss quality, namely 9.68% for the vaccine room node, 13.4% for the medicine room, and the average temperature and humidity. Vaccine room is 24°C and 60%, while in Medicine room is 26°C and 50%. And the average temperature and humidity in the Vaccine room were 24°C and 60%, while in the Medicine room it was 26°C and 50%. This difference occurs due to several factors such as the location of the room, the area of the room, and the number of people in the room.